Constitutional Reforms in Kazakhstan: were they participative and responsive? - Imanaliyev, Zhandos; Zhumabekov, Nariman (Nazarbayev University Graduate School of Public Policy, 2017)
Twenty-five years after the Republic of Kazakhstan became independent ‘almost by accident’, the continuous improvement of the country's governance system is on the top of its political agenda. Over the last years, decision-makers in Astana have been working hard to improve Kazakhstan’s governing structures on all levels, realizing that the future development of the country depends on the quality of political decision-making, effective policy implementation, and accountable communication between the state’s institutions and citizens. Especially the latter point has been highlighted as crucial for improving the young Republic’s democracy, and for making it last. In this thesis, we study President Nursultan Nazarbayev’s recent decision to transfer central aspects of presidential power onto other branches of the government, thereby strengthening the role of the Parliament as the supreme representative body exercising legislative power. To do so, we analyze the most recent wave of constitutional reform from the perspective of the government, citizens, and the international community; and compare developments in Kazakhstan with similar reforms taking place in other countries. To contextualize our claims, we also explore the constitution of Kazakhstan, paying special attention to how, when and by whom it was written, and what kind of amendments were made to it over time. The main Research Question of this thesis is why and by whom recent constitutional reform were initiated, and whether they were participative or responsive in nature. In answering this question, we attempted to measure the effectiveness of implementing recent reforms through conducting surveys among interested groups, opinion polls, and analysis of other data sources. On the basis of these data, we consider whether – and if yes, how - recent reforms will give impetus to the development of democratic structures in Kazakhstan, and contribute to the well-being of its people....
Keywords: public policy; democracy; well-being of people; participative and responsive reforms; constitutional reforms in Kazakhstan; public opinion